Asas Hukum Yang Berkaitan Dengan Kurator Dalam Menjalankan Tugasnya Sebagai Pelaksana Putusan Pengadilan Niaga Dalam Perkara Pailit - Fadel Muhammad (RIO LAW JURNAL, 2021)
Bankruptcy is general confiscation of all property owned by the Debtor who is declared bankrupt by a legally binding decision or inkracht van gewijsde where in this case the management and settlement is carried out by a curator appointed by the Commercial Court under the supervision of the Supervisory Judge. In carrying out its duties, the curator is not only about how to save the bankruptcy assets that have been collected and then distributed to creditors, but as far as possible can increase the value of the bankruptcy assets. Thus, curators are required to have integrity that is guided by truth and justice and must comply with professional and ethical standards with the aim of avoiding conflicts of interest with debtors and creditors. Based on the description above, the author is interested in writing about the legal principles of the curator's functions and duties as executor of the bankruptcy decision against the Debtor at the Commercial Court. This research method is normative juridical. As for the results of the research and discussion that there are three principles used by the curator in carrying out his function as executor of the decision of the Commercial Court in a bankruptcy case, the principle of justice for a curator is being able to be fair when recording all bankruptcy assets, whether hidden or real, seeking or maximizing bankruptcy assets, maintaining or increasing the value of bankruptcy assets, selling bankruptcy assets at the maximum price, In general it can be said that balance is a condition in which there is harmony or harmony, and is not biased or skewed on certain matters, taking into account the proportions of each. each of the components that surround it. The provisions regarding the principle of independence are emphasized in the Code of Ethics for the Indonesian Curators and Administrators Association (AKPI) which states that in every appointment received, members of the Indonesian Curators and Administrators Association (hereinafter referred to as “members”) must be independent and free from any influence. Keywords: Legal Principles, Curator, Executor of Commercial Court Decisions in Bankruptcy Cases. Abstrak19Kepailitan adalah sita umum terhadap semua kekayaan yang dimiliki oleh Debitor yang dinyatakan pailit oleh putusan yang telah berkekuatan hukum tetap atau inkracht van gewijsde dimana dalam hal ini pengurusan dan pemberesannya dilakukan oleh Kurator yang ditunjuk oleh Pengadilan Niaga di bawah pengawasan Hakim Pengawas. Dalam menjalankan tugasnya Kurator tidak sekadar bagaimana menyelamatkan harta pailit yang berhasil dikumpulkan untuk kemudian dibagikan kepada para kreditor tapi sedapat mungkin bisa meningkatkan nilai harta pailit tersebut. Dengan demikian, Kurator dituntut untuk memiliki integritas yang berpedoman pada kebenaran dan keadilan serta keharusan untuk menaati standar profesi dan etika dengan tujuan untuk menghindari adanya benturan kepentingan dengan Debitur maupun Kreditur.Berdasarkan uraian diatas penulis tertarik untuk melakukan penulisan mengenai asas hukum dari fungsi dan tugas Kurator sebagai pelaksana dari putusan pailit terhadap Debitur pada Pengadilan Niaga. Metode penelitian ini adalah yuridis normatif. Adapun hasil dari penelitian dan pembahasannya Bahwa ada tiga asas yang di pakai Kurator dalam melaksanakan fungsinya sebagai pelaksana putusan Pengadilan Niaga dalam perkara pailit, Asas keadilan bagi seorang Kurator adalah mampu bersikap adil ketika mencatat seluruh harta pailit baik harta yang tersembunyi maupun yang nyata, mencari atau memaksimalkan harta pailit, menjaga atau meningkatkan nilai harta pailit, menjual harta pailit pada harga maksimal, Secara umum dapat dikatakan bahwa keseimbangan adalah suatu keadaan dimana  terdapat keserasian atau keharmonisan, dan tidak dalam kecenderungan berat sebelah atau condong pada hal tertentu, dengan memperhatikan proporsional  masing-masing komponen-komponen yang melingkupinya. ketentuan  mengenai prinsip independensi dipertegas dalam Kode Etik Asosiasi Kurator dan Pengurus Indonesia (AKPI) yang menyatakan dalam setiap penunjukan yang diterima, anggota Asosiasi Kurator dan Pengurus Indonesia (selanjutnya disebut “anggota”) harus independen dan bebas dari pengaruh siapapun Kata Kunci: Asas Hukum, Kurator, Pelaksana Putusan Pengadilan Niaga Dalam Perkara Pailit.